Lower-limb muscle strength, anterior-posterior and inter-limb asymmetry in professional, elite academy and amateur soccer players - Beato, M.; Young, D.; Stiff, A.; Coratella, G. (Journal of Human Kinetics, 2021)
Given the importance of the lower-limb strength and strength balance in soccer players and its relationship with injury prevention and performance, the present study compared quadriceps and hamstrings strength, the conventional (Hconc:Qconc), functional (Hecc:Qconc) hamstrings-to-quadriceps ratio and inter-limb strength asymmetry in professional, elite academy and amateur male soccer players. In this cross-sectional study, two hundred-six soccer players (professional = 75, elite academy = 68, amateurs = 63) volunteered to participate. Quadriceps and hamstrings isokinetic peak torque was investigated at 60°.s-1 in both the concentric and eccentric modality and at 300°.s-1 in the concentric modality. The conventional Hconc:Qconc, functional Hecc:Qconc ratio and quadriceps and hamstrings inter-limb strength asymmetry were then calculated. Professional players presented greater quadriceps and hamstrings strength than elite academy (effect size from small to moderate) and amateur players (moderate to very large). Both the conventional Hconc:Qconc and functional Hecc:Qconc ratio were greater in professional than elite academy and amateur players (small to moderate). Overall, quadriceps and hamstrings inter-limb strength asymmetry was greater in amateurs than professional (small to very large) and elite academy (trivial to large) players. The present findings provide coaches and medical staffs with normative lower-limb muscle strength data on professional, academy and amateur soccer players. Overall lower-limb muscle strength and inter-limb strength asymmetry could be used to evaluate possible inference on injury prevention and performance. The hamstrings-to-quadriceps ratio poorly differentiates between the soccer players background and offers limited prediction for injury prevention and performance.